Quality Of Patient Care For Health Insurance Participants Community At Empagae Health Center Sidenreng Rappang District - Andang, Baharuddin (Sean Institute, 2024)
The title of this study is The Quality of Jamkesmas Members' Health Service at Empagae Public Health Center, Sidenreng Rappang Regency, South Sulawesi. The purpose of this study is to give the understanding about public health service through the program of Jamkesmas as there are still many citizens complaining about the quality of the service given by Empagae Public Health Centre in order to enhance the quality of further health service to be more effective. This study uses the analytical descriptive method with the qualitative technique in the data processing. In this study, the public health service covers four aspects including the easiness in dealing with the problem, getting the appropriate service, getting the equal treatment, getting the transparent and honest treatment. The result of the analysis shows that there is a lack of clear instructions, the honesty, the security, and the equality of giving the treatment by the officers to the patients of Jamkesmas.